Budidaya Magot Sebagai Strategi Pengelolaan Limbah Organik: Pengabdian - Handayani, Aniek Sri; Octasylva, Anuridya Rosyidta Pratiwi; Syafril, Enjarlis; Susilawati, Sri Endah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Maggot larvae play a crucial role in the decomposition of organic waste, reducing waste volume while producing high-value products such as animal feed and organic fertilizer. This Community Service Program (Abdimas) is designed to optimize Maggot products as a potential solution for organic waste management, while simultaneously improving the economic resilience of micro, small, and medium enterprises (MSMEs). The program begins with coordination activities and an initial survey to assess the needs and conditions of MSMEs, followed by financial literacy training and a marketing strategy workshop to strengthen partners' managerial skills. Subsequent mentoring sessions emphasize product development, packaging innovation, and strengthening market competitiveness. The program's results indicate that Maggot product development has the potential to drive the economy for MSMEs, while providing an environmentally friendly approach to organic waste management and encouraging positive impacts on the community. Furthermore, the application of technology introduced by the Community Service Team has resulted in increased revenue for maggot businesses, specifically for MSMEs in Tangerang Regency, and opened up new opportunities for future business development.